Food, Fun and Fitness Leader's Guide - Linda Cook; Joy C. Jordan; Henry Leath (EDIS)
Produced by the Department of Family, Youth and Community Sciences and the Florida 4-H Youth Development Program, Institute of Food and Agricultural Sciences, University of Florida Cooperative Extension, May 1996. Revised March 1997; reviewed June, 2002.